Artificial intelligence management in tertiary education in order to improve the quality of knowledge and reduce the risks of learning - V. F. Ukolov; O. V. Trofimenko (Вестник университета)
The subject of the article is the management of artificial intelligence in the field of higher education, which improves the quality of knowledge and reduces the risks of learning in the context of digitalization. The purpose of the article is to identify the problems hindering the development of artificial intelligence in higher education and to develop recommendations for their solution. The research methodology is based on the use of modern methods, techniques and tools in the study of artificial intelligence, allowing to take into account the impact on the education quality, on the psychology participants in the educational process and on the mechanisms for managing its development. The main results obtained in the article provide answers to ambiguous questions about the feasibility of large-scale use of artificial intelligence in education, its dominance among other methods of knowledge transfer and its application in its pure form, without live communication with teachers. The answers received in the article convince the opponents of this topic that the use of the author’s developments regulating the use of artificial intelligence in education leads to an increase in the quality of education and neutralizing the emerging risks of learning from a new generation. The article reveals ethical shortcomings and shows the advantages of the artificial intelligence technologies use in the practice of tertiary education. The main conclusions made in the article are based on the statement that the artificial intelligence system in the field of tertiary education needs to be regulated and managed by development using the methods of psychological, organizational, regulatory and technological character proposed by the authors.